Digital Marketing to Increase Sales of Fishery Products for MSMEs in Biringkanaya District - Muh Rifkhi Ramadhan; Sri Suro Adhawati; Amiluddin Amiluddin; Arie Syahruni Cangara; Sitti Fakhriyyah; Sutinah Made; Aris Baso; Benny Audy Jaya Gosari (PONGGAWA : Journal of Fisheries Socio-Economic, 2026)
Digital marketing has proven to be an effective solution for boosting sales of fishery products by MSMEs in Biringkanaya District, Makassar City. This study aims to analyze the implementation of digital marketing strategies by MSMEs, measure their impact on sales growth, and identify the factors influencing their implementation. This study employs a quantitative descriptive method, involving 11 MSMEs operators with data collected through questionnaires, in-depth interviews, and observations. Data analysis utilized multiple linear regression to test the significance of digital marketing’s role. The results indicate that 82% of MSMEs have adopted digital marketing, with some businesses experiencing a significant revenue increase of up to 860%. However, challenges such as a lack of technical training and internet infrastructure remain barriers. The results of the partial T-test indicate that sales effectiveness (X2) and marketing techniques (X4) have a significant impact on digital marketing, while the other four variables do not. This confirms that the success of digital marketing is more influenced by marketing strategies than by the educational background or age of the business owners. These findings highlight the importance of ongoing training, mentoring, and infrastructure improvements to support the digital transformation of MSMEs. This study makes a strategic contribution to supporting the development of digital marketing to enhance the competitiveness of MSMEs in the fisheries sector.